SENSORY PREFERENCE DETERMINATION OF GREEN TEA EXTRACTS FROM UNCONTROLLED AND RELAY-CONTROLLED BREWING PROCESSES USING RANK ORDER CENTROID AND SIMPLE ADDITIVE WEIGHTING - Pratama, Borneo Satria; Alfiqriyansyah, Alfiqriyansyah; S, Arya Dwicahya; Rukmana, Fitri Hardiyanti; Hartati, Intan Dwi; Cahya Brutu, Henrike Lehla; Winda, Winda; Sariati, Sariati (Jurusan Teknik Mesin Fakultas Sains dan Teknik Universitas Bangka Belitung, 2024)
Green tea extract is a popular beverage known for its health benefits. To increase its market appeal, understanding the sensory profiles—taste, aroma, and color—of green tea extract is essential to ensure customer satisfaction. In this study, experiments were conducted to determine the optimal extraction conditions by varying extraction times (3 or 6 minutes) and temperatures (60°C, 80°C, or 100°C) in two brewing methods: (1) a relay-controlled brewing system utilizing Arduino, and (2) a standard brewing process without automated control. Sensory evaluations were conducted by 30 untrained panelists using a 9-point hedonic scale.. Decision-making methods, Rank Order Centroid (ROC) and Simple Additive Weighting (SAW), were then applied to identify the most preferred product. Results indicated that the highest taste score was achieved by the 80°C-6 min sample, while the best aroma and color scores were observed in the 100°C-3 min sample. Overall, the decision-making process using the combination of ROC and SAW methods concluded that the green tea extract from the 100°C-3 min sample was the most preferred by the panelists.